Information theoretic security : 9th International Conference, ICITS 2016, Tacoma, WA, USA, August 9-12, 2016, Revised selected papers /: 9th International Conference, ICITS 2016, Tacoma, WA, USA, August 9-12, 2016, Revised selected papers. (2016) - Unknown
No abstract available